2006
DOI: 10.1111/j.1750-3639.2006.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6 and Multiple Sclerosis: A One-Year Follow-up Study

Abstract: A higher HHV-6A frequency of active infection (reactivation or new infection) would lead to a more frequent exposure of HHV-6A antigens to the immune system of RRMS patients; this active replication of HHV-6A seems to be specifically related with the exacerbations in a subset of RRMS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
45
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 62 publications
9
45
3
1
Order By: Relevance
“…In previous studies of our group, we have reported that the presence of HHV-6A/B DNA in blood and serum during IFN-beta treatment could be a good marker of poor response [18][20]. Similar results were found by other authors in MS patients treated with IFN-beta when serum cell-free DNA of HHV-6A/B was analyzed [21].…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies of our group, we have reported that the presence of HHV-6A/B DNA in blood and serum during IFN-beta treatment could be a good marker of poor response [18][20]. Similar results were found by other authors in MS patients treated with IFN-beta when serum cell-free DNA of HHV-6A/B was analyzed [21].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, although an overwhelming majority of post-transplant reactivation occurs with HHV-6B [28, 29, 53], HHV-6A DNA and mRNA are found more frequently than HHV-6B in patients with neuroinflammatory diseases such as multiple sclerosis (MS) [9, 14, 48, 115] and rhomboencephalitis [37]. HHV-6A has been found predominantly in the CNS of a subset of patients with MS, and active HHV-6A infection has been detected in blood [8, 9, 11] and in CSF [110] of patients with relapsing/remitting MS [810, 14, 20, 110, 115, 131]. Marmosets inoculated with HHV-6A intravenously exhibited neurological symptoms, whereas those inoculated with HHV-6B were asymptomatic [75].…”
Section: Distinct Epidemiology and Disease Associationsmentioning
confidence: 99%
“…Factors could include: ambient environmental factors (such as sunlight, rainfall, ozone or particulate matter [18] ); a cyclic fluctuation in the incidence of infections [6] and related physiological changes (including epidermal vitamin D synthesis, release of melatonin and interferon-␥ production [19] ). MS relapses have been linked with an array of infectious micro-organisms, including viral, bacterial and parasitic [6,10,11,[20][21][22][23][24][25][26][27] . However, it is possible that infections are also influenced by monthly vitamin D, as higher levels boost innate immunity [28] .…”
mentioning
confidence: 99%